DELEGATION OF CLINICAL MANDATE IN ANESTHESIOLOGY: A LEGAL AND CHALLENGES PERSPECTIVE - Kresnahadi, Ananda Agus (Journal Philosophy of Law, 2024)
This study aims to critically analyze the delegation of authority for anesthesia and sedation procedures from anesthesiology and intensive care specialists to nurses or anesthesia assistants, and to examine the conformity of such practices with the prevailing legal framework in Indonesia. The research focuses on clarifying the boundaries of authority, legal protection for healthcare workers, and the effectiveness of regulations in ensuring patient safety. This is a normative juridical study using statutory and empirical approaches. Data were obtained through literature review of relevant legislation and in-depth interviews with anesthesiology specialists, nurse anesthetists/anesthesia assistants, and hospital administrators in several regions. The findings reveal that although the delegation of authority is normatively permitted under various regulations—such as Law No. 17 of 2023, Government Regulation No. 28 of 2024, and relevant Ministerial Regulations—its implementation in practice faces significant challenges. Regulatory disharmony, dual nomenclature between certified nurse anesthetists and anesthesia assistants, and the absence of clear professional standards have created legal uncertainty and inter-professional conflicts. On the other hand, these professionals have played a crucial role in providing anesthesia services, especially in regions with limited access to anesthesiologists. Therefore, a comprehensive regulatory reconstruction and restructuring of professional standards are urgently needed to ensure that delegation of authority is carried out safely, legally, and equitably, thereby strengthening a more accessible, equitable, and high-quality national health service system.